The effects of dietary omega 3 fatty acids on platelet composition and function in man: a prospective, controlled study - Goodnight, SH Jr; Harris, WS; Connor, WE (Blood, 1981)
The rarity of atherosclerotic vascular disease and a mild bruising tendency in Greenland Eskimos has been linked to their ingestion of omega 3 fatty acids contained in foods obtained from the sea. Previous studies have shown that feeding salmon oil to normal volunteers resulted in reductions of plasma cholesterol and triglycerides. We wished to learn whether salmon oil feeding would result in the incorporation of omega 3 fatty acids into platelets and whether platelet function or platelet-vessel interaction would be altered. Diets containing salmon oils led to the incorporation of eicosapentaenoic acid (C20:5 omega 3) into platelets (6.1%) with a reduction in arachidonic acid (C20:4 omega 6). The ratio of C20:5/C20:4 increased from 0.0045 on the control diet to 0.3 on the salmon diet. Bleeding times were prolonged (from 6.75 to 10 min, p less than 0.005), platelet retention on glass beads was mildly reduced (from 89% to 78%, p less than 0.0005), and platelet aggregation in response to dilute concentrations of ADP was inhibited in the subjects ingesting the salmon oil. We conclude that in normal subjects dietary omega 2 fatty acids derived from salmon oil are incorporated into platelet phospholipids and that these changes are accompanied by alterations in bleeding time and platelet function.